Reducing Student’s English Dialogue Anxiety in Online Learning through Board Game - Rahma Nuzulia; Catur Kepirianto (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2020)
The COVID 19 has been going on since April 2020 in Indonesia. It has resulted in the Indonesian government, especially the Ministry of Education and Culture, taking preventive steps to minimize contracting the virus. One of them is using online learning for students to go to school. However, there are challenges for teachers and students while learning in an online class, such as students who are often absent, students will quickly feel bored, students tend to be passive in the learning process, students do not master the learning material, and much more. It also happens in an English lesson, especially a dialogue activity. This research aims to prove whether using a board game can be effective media to reduce students’ language anxiety level or not during English learning in an online classroom. The kind of board game is the combination between snake and ladder and candy land, or it has been modified based on learning purpose. The research design used in this research is a quasi-trial non-equivalent control group design. The samples of this research are 60 ninth grades of junior high school students which are divided into the trial and control group. Data analyses used in this research are using SPSS mean score, data deviation, while hypothesis testing used in this research is the Mann-Whitney test.  The result showed that a board game can reduce students’ anxiety levels. The data showed that the mean score of students after implementing board game reduces by 2.90 points, while the standard deviation increases by 2.901 points. From the Mann-Whitney test, it is known that Asymp. Sig. (2-tailed) is 0.003 or < 0.05 which shows that H0 is rejected, and H1 is accepted. From the data analysis, it can be shown that the board game is effective media to reduce students’ language anxiety in dialogue activity during learning in an online class. Keywords: board game, language anxiety, online learning